A comparison of drug substance predicted chemical stability with ICH compliant stability studies. (4th March 2019) - Williams, H. E.; Bright, J.; Roddy, E.; Poulton, A.; Cosgrove, S. D.; Turner, F.; Harrison, P.; Brookes, A.; MacDougall, E.; Abbott, A.; Gordon, C.
Abstract: Objective: The aim of this study is to demonstrate the applicability of predictive stability studies to the degradation of drug substances. Significance: The use of predicted stability studies during pharmaceutical development and in regulatory submissions is increasing, particularly in early phase to support an initial retest period/shelf life claim in the absence of standard stability data. These studies offer an alternative to standard stability testing and can facilitate clinical trials to be started earlier and medicines to reach patients faster. They involve a short-term stressed stability study, typically designed to degrade a drug substance or product to the specification level of the shelf life limiting attribute. The results are used to predict degradation under long-term storage conditions and enable stability understanding to be gained over a short time frame, using limited amounts of material. Methods: In this work, Accelerated Stability Assessment Program (ASAP) studies were performed for 10 different drug substances and the predictions obtained for chemical degradation were compared to ICH compliant stability data. Results: Across the studies good agreement was achieved, with the initial retest period predictions from the ASAP studies being conservative by design. When minimal degradation was observed during an ASAP study, it was demonstrated that at least a 12-month initial retest period could be supported. Conclusion: This comparison of ASAP predictions and ICH compliant stability data has demonstrated the ability of well-designed ASAP studies to predict the long-term chemical stability of drug substances.